A re-examination of the molecular systematics and phylogeography of taxa of the Peromyscus aztecus species group, with comments on the distribution of P. winkelmanni - Kilpatrick, C. William; Pradhan, Nelish; Norris, Ryan W (THERYA, 2021)
The objectives of this study are to examine the available molecular data from the mitochondrial cytochrome-b gene (Cytb) and a concatenated dataset with this gene and two nuclear introns (Adh-1-I2 and Fgb-I7) to reexamine the systematic and phylogeographic conclusions reached by Sullivan et al. (1997) concerning the Peromyscus aztecus species group. The divergence of samples of P. aztecus oaxacensis across the Isthmus of Tehuantepec are further examined and taxonomic revisions are suggested. In addition, this study reviews the sources of data that lead to the conclusion that P. winkelmanni occurred in the Sierra Madre del Sur in Guerrero including a morphometric examination of a reported voucher. Bayesian and maximum likelihood analyses were conducted on a dataset of 31 Cytb sequences of all taxa in the P. aztecus group except for P. a. cordillerae and a concatenated dataset including five individuals of this group. Representative taxa of the P. boylii, P. mexicanus, and P. truei groups were included in both analyses. Body and cranial measurements of the voucher of the P. winkelmanni from Guerrero from which a Cytb sequence is reported to have been obtained was compared with measurements from specimens taken from the vicinity of Dos Aguas, Michoacán, including the type locality. We identified seven instances involving problematic identifications in GenBank. Once these issues were addressed, well-supported monophyletic sister clades of the P. aztecus and P. boylii species groups were recovered from phylogenetic analyses of Cytb sequences (Fig 1). Phylogenetic analyses of the Cytb and the concatenated datasets recover similar topologies that support the relationships of taxa of the aztecus group proposed by an earlier molecular study. Populations of P. a. oaxacensis southeast of the Isthmus of Tehuantepec represent a distinct species. Measurements of the voucher from Guerrero identified as the source of a P. winkelmanni Cytb sequence are smaller than P. winkelmanni for several characters. The divergent populations of P. a. oaxacensis from southeast of the Isthmus of Tehuantepec are recognized as two subspecies of P. cordillerae, P. c. cordillerae and P. c. hondurensis, whereas those northwest of the Isthmus are retained as P. a. oaxacensis. The lack of genetic divergence observed between P. a. evides and P. a. oaxacensis questions whether these two taxa should continue to be recognized as separate subspecies. Northern and southern populations of P. spicilegus demonstrate moderate divergence and additional examination of morphological and molecular differentiation within this taxon is warranted. The distribution of P. winkelmanni should be restricted to the vicinity of Dos Aguas, Michoacán, due to the lack of a voucher specimen that would confirm its reported occurrence in Guerrero.